The Taxation of Couples - Felix J. Bierbrauer; Pierre C. Boyer; Andreas Peichl; Daniel Weishaar (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the tax treatment of couples. We develop two different approaches. One is tailored to the analysis of tax systems that stick to the principle that the tax base for couples is the sum of their incomes. One is tailored to the analysis of reforms toward individual taxation. We study the US federal income tax since the 1960s through the lens of this framework. We find that, in the recent past, realizing efficiency gains requires lowering marginal tax rates for secondary earners. We also find that revenue-neutral reforms towards individual taxation are in the interest of couples with high secondary earnings while couples with low secondary earnings are worse off. The support for such a reform recently passed the majority threshold. It is rejected, however, by a Rawlsian social welfare function. Thus, there is a tension between Rawlsian and Feminist notions of social welfare.
Keywords: C72; D72; D82; H21; 330; taxation of couples; tax reforms; optimal taxation; political economy; non-linear income taxation